Radial Solutions of Free Boundary Problems for Degenerate Parabolic Equations (Journal of Partial Differential Equations, 1990)
ln this paper we are devoted to the free boundary problem {u_t = &#916A(u) \quad (x,t) &#8712 G_{r,r} u(x, 0) = &#966(x) \quad &#8712 G_0 u|_r = 0 (\frac{&#8706A(u)}{&#8706x_i}v_i + &#968(x)v_1)|_r = 0, where A'(u) &#8805 0. Under suitable assumptions we obtain the existence and uniqueness of global radial solutions for n =2 and local radial solutions for n &#8805 3.